Fructose overfeeding in first‐degree relatives of type 2 diabetic patients impacts energy metabolism and mitochondrial functions in skeletal muscle. Issue 12 (12th September 2016) - Seyssel, Kevin; Meugnier, Emmanuelle; Lê, Kim‐Anne; Durand, Christine; Disse, Emmanuel; Blond, Emilie; Pays, Laurent; Nataf, Serge; Brozek, John; Vidal, Hubert; Tappy, Luc; Laville, Martine
Abstract : The high‐fructose diet induces profound effects on skeletal muscle genes expression (lipogenesis, fatty acid entry in mitochondria, β‐oxidation, and respiratory chain) supporting the whole‐body metabolic shift with the preferential use of carbohydrates instead of lipids contributing to reorientate lipids toward storage. This study supports the concept that overconsumption of fructose could contribute to metabolic disorders in humans. Abstract : Scope: The aim of the study was to assess the effects of a high‐fructose diet (HFrD) on skeletal muscle transcriptomic response in healthy offspring of patients with type 2 diabetes, a subgroup of individuals prone to metabolic disorders. Methods and results: Ten healthy normal weight first‐degree relatives of type 2 diabetic patients were submitted to a HFrD (+3.5 g fructose/kg fat‐free mass per day) during 7 days. A global transcriptomic analysis was performed on skeletal muscle biopsies combined with in vitro experiments using primary myotubes. Transcriptomic analysis highlighted profound effects on fatty acid oxidation and mitochondrial pathways supporting the whole‐body metabolic shift with the preferential use of carbohydrates instead of lipids. Bioinformatics tools pointed out possible transcription factors orchestrating this genomic regulation, such as PPARα and NR4A2. In vitro experiments in human myotubes suggested an indirect action of fructose in skeletal muscle, which seemed to be independent from lactate, uric acid, or nitric oxide. Conclusion: This study shows therefore that a large cluster of genes related to energy metabolism, mitochondrial function, and lipid oxidation was downregulated after 7 days of HFrD, thus supporting the concept that overconsumption of fructose‐containing foods could contribute to metabolic deterioration in humans.